EFEK DENTOSKELETAL PADA MALOKLUSI KELAS II DIVISI 1 DENGAN BIONATOR DAN ALAT ORTODONTI LEPASAN : LAPORAN KASUS - Sari Kurniawati; Angela Putri Bunga Senanda (Odonto : Dental Journal, 2019)
Background: Class II division 1 malocclusion characterized by mandibularretrognation, deep bite and increasement of overjet. Myofunctional appliance could modify the growth and developmental of mandibular at appropriate phase. The purpose of this case report was to present successful management of Class II division 1 by using bionator and removable appliance.Case Management: A 9 years old girl with upper teeth protrusion, crowding and affected the esthetical perception. The diagnosis was Class II division 1 with mandibular retrognation and upper incisor protrusion, upper and lower anterior crowding and palatal bite. Patient also had lip biting and thumb sucking habit. Bionator leads the mandibular moved forward and arch widening. Treatment planning were to reduce overjet by prognating mandibular and bad habit elimination. Followed by retracting the upper teeth and deep bite correction by using removable appliance.Conclusion: Patient profile became corrected in 10 weeks. Overjet reduced in by prognating the mandible, decreasing of palatal bite, molar relation become Class I and bad habit elimination. In 10 months, overjet and overbite were corrected.